Protective Effect of Tetrandrine in a Rabbit Model of Osteoarthritis - Fengfeng WU,; Juntao XU,; Zaihua ZHU, (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the antiinflammatory effect of tetrandrine in a rabbit model of osteoarthritis. Materials and methods: The cruciate ligaments and medial menisci of 36 female New Zealand white rabbits (each weighing 2.0-3.0 kg) were resected. Six weeks after surgery, the animals were randomly divided into three groups (n=12 in each): tetrandrine (20 mg/kg/day), indomethacin (3 mg/kg/day) and control (saline 10 mL/day) groups. After 14 days of treatment, the results were assessed by macroscopic observation, histological evaluation, measurement of the levels of interleukin-1 beta, tumor necrosis factor-alpha and nitric oxide in the synovial fluid and messenger ribonucleic acid expression of metalloproteinase-3 in synovia. Results: In the tetrandrine group, the pathological changes were more attenuated than in the control group. Levels of interleukin-1 beta, tumor necrosis factor-alpha, nitric oxide and metalloproteinase-3 in the synovial fluid or synovium were all significantly suppressed in the tetrandrine group compared with the control group. There were no significant differences between the tetrandrine and indomethacin groups. Conclusion: The results of this study demonstrate that tetrandrine may protect against the development of experimentally induced osteoarthritis.